Removal of adhesive powders from additive-manufactured internal surface via electrochemical machining with flexible cathode - Zhao, Chenhao; Qu, Ningsong; Tang, Xiaochuan (Precision engineering, 2021)
Additive manufacturing (AM) is a rapidly developing technology that has attracted considerable interest in industry because of its tremendous advantages. However, the inferior surface quality of AM components, particularly the partially melted powders adhering to the surface, restricts the functionality of the as-printed parts. In particular, the internal hole is more challenging to finish because of its poor visibility. This study proposed an electrochemical machining (ECM) process that employed a salt solvent to finish an internal surface produced using AM. This ECM process could reduce the topographical fluctuation of the surface by eliminating the adhesive powders and removing the band protrusions caused by the laser melting process. This reduced the surface roughness (Sa) values of a straight hole from 14.151 to 6.287 μm. The proposed ECM process was also effective at finishing the internal surface of a curving hole produced using AM, which is complicated to handle using many other machining methods. In this process, a flexible cathode insulated by several blocks moved across a curving internal hole in a reciprocating manner to perform the electrochemical dissolution. The adhesive powders on the curved surface could be eliminated, and the surface asperities could be removed, with the Sa values reduced from 15.522 to 8.102 μm. •An ECM process is proposed to finish the AM internal hole with eliminating adhesive powders.•A flexible cathode tool is particularly fabricated to finish the AM curving internal hole.•The removal process of AM surface asperities is thoroughly investigated.